2020
DOI: 10.1002/fsn3.1800
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH on the chemical and structural interactions between apple polyphenol and starch derived from rice and maize

Abstract: To date, how pH affects starch–polyphenol mixtures has not been thoroughly investigated. This study explored the impact of combining apple polyphenol (AP) with both normal rice starch (NRS) and normal maize starch (NMS) across a range of pH conditions. NRS–AP mixture particle sizes across a pH range of 3–8 varied from 169.9 ± 5.4 to 187.5 ± 6.9 μm, while for NMS–AP particles, these sizes ranged from 161.8 ± 8.0 to 176.0 ± 4.9 μm, indicating that the aggregation of starch–AP was inhibited under low pH condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Several authors reported that the main reason for the encapsulation of phenolic compounds with starch is due to the formation of hydrogen bonds (between the hydroxyl and carboxylic groups of GA and oxygen atoms of the glycosidic linkages of starch) and not by an amylose inclusion complex. 1,41 We postulated that the higher number of single helices in the endogenous lipid-amylose complex present in PeS, corroborated by DSC measurement, could positively contribute to the intrachain entrapment of GA.…”
Section: Solubility and Swellingmentioning
confidence: 83%
“…Several authors reported that the main reason for the encapsulation of phenolic compounds with starch is due to the formation of hydrogen bonds (between the hydroxyl and carboxylic groups of GA and oxygen atoms of the glycosidic linkages of starch) and not by an amylose inclusion complex. 1,41 We postulated that the higher number of single helices in the endogenous lipid-amylose complex present in PeS, corroborated by DSC measurement, could positively contribute to the intrachain entrapment of GA.…”
Section: Solubility and Swellingmentioning
confidence: 83%
“…Phenolic molecules can form inclusion or noninclusion complexes or intermolecular aggregates with starch molecules through hydrophobic interaction (Chou et al., 2020; Zhao, Sun, et al., 2019), hydrogen bonds (Wang, Wang, et al., 2021; Wang et al., 2018), CH–π bonds (Wang et al., 2021b), and/or van der Waals forces (Amoako & Awika, 2019). Phenolic compounds (ligand molecules) can be bound in the cavity of the helix (Sudlapa & Suwannaporn, 2023), between helices in the crystallization regions (Guo et al., 2019), or in the amorphous regions (Zhang et al., 2020; Zhao, Wang, et al., 2019), as shown in Figure 1.…”
Section: Effects Of Food Processing On the Formation Of Starch–phenol...mentioning
confidence: 99%
“…Typical structures representing the formation of the V‐type inclusion complexes can be characterized using differential scanning calorimetry (DSC), X‐ray diffraction (XRD), or nuclear magnetic resonance (NMR) techniques (Chou et al., 2020; Liu et al., 2019; Zhao, Sun, et al., 2019; Zhao, Wang, et al., 2019). The complexes show melting endotherms at a temperature exceeding 90°C using DSC (Obiro et al., 2012), and the V‐type crystalline peaks at 7.5°, 13°, and 19.9° of 2 θ (Chai et al., 2013) using XRD.…”
Section: Effects Of Food Processing On the Formation Of Starch–phenol...mentioning
confidence: 99%
See 1 more Smart Citation
“…XRD is an effective technique to characterize the formation of complexes between starch and phenolics, including non-inclusion complexes [37][38][39] or V-type inclusion complexes [40][41][42]. Compared with native starch with typical peaks of A-type crystallites (Figure 1), XRD patterns of cold extruded starch in the absence and presence of phenolics (CE-S and CE-S-P2) showed typical diffraction peaks of A+V-type crystallites with less pronounced peaks at 12.8 1) [43], indicating that the cold extrusion altered the starch crystalline structure, which is consistent with the results of the cold extruded wheat starch [44].…”
Section: Characteristics Of Starch-phenolic Complexes Induced By Extr...mentioning
confidence: 99%